The Effectiveness Of Scaffolded Writing Strategy On Students’ Writing Skill Viewed From Students’ Critical Thinking - Anita Budi Rahayu (STKIP PGRI Nganjuk, 2018)
This research is aimed at finding out: (1) whether in general Scaffolded Writing Strategy is more effective than conventional writing for teaching writing; (2) which ones students who have highcritical thinking have better writing skill than those having low critical thinking; and (3) whether or not there is an interaction between teaching techniques and students’ critical thinking. The experimental class was taught by using Scaffolded Writing Strategy whereas the control classwas taught by conventional Writing Strategy. Each class was divided into two groups in whicheach consists of students having high critical thinking and those having low criticalthinking. To gain the data, two instruments were used namely writing test and criticalthinking test. The data were analyzed by using Multifactor Analysis of Variance ANOVA 2x2and Tukey test. Before conducting the ANOVA test, pre-requisite test namely normality andhomogeneity test were conducted. The findings of this research are: (1) Scaffolded Writing Strategy is moreeffective than coventional Writing Strategy to teach writing; (2) The students having highcritical thinking have better writing skill than those having low critical thinking; and (3)There is an interaction between teaching strategies and students’ critical thinking inteaching writing. Therefore, it is recommended for English teachers to implement Scaffolded Writing Strategy inteaching writing because this strategy helps the students to improve writing skill andencourages them to be active learners.